The Spirit Speaks and the Wind Blows: The Primary Meaning of Πνεῦμα in John 3:8 - Christopher James Luthy (Sekolah Tinggi Theologia Jaffray, 2020)
This paper addresses the double-meaning of Spirit and wind in John 3:8 and argues that the verse should be translated in terms of the Spirit. The study begins with an analysis of the Greek text of John 3:8. It is demonstrated that even though a double-meaning is present, the more appropriate interpretation is the Spirit reading. Arguments in favor of the wind interpretation of John 3:8 are also addressed. Following this, the study surveys all usages of John 3:8 in the early church writings. It is concluded that in the writings of the Ante-Nicene Fathers, the text was interpreted with the Spirit. It is also concluded that the vast majority of Nicene and Ante-Nicene church fathers understood John 3:8 with the Spirit. Therefore, it is suggested that the recent preference of the wind meaning, which is evident in many current English translations, should be revised such that the Spirit reading becomes primary.